Outcomes of Artificial Urinary Sphincter Implantation in Patients with Detrusor Underactivity and Postprostatectomy Incontinence - Han, Kyu Hun; Kim, Joon Chul; Bae, Woong Jin; Choi, Jin Bong; Koh, Jun Sung; Cho, Kang Jun (Urology Journal, 2023)
Purpose: There is insufficient evidence for postoperative outcomes of artificial urinary sphincter (AUS) implantation for postprostatectomy incontinence (PPI) with detrusor underactivity (DU). Thus, we assessed the impact of preoperative DU on the outcomes of AUS implantation for PPI. Materials and Methods: Medical records of men who underwent AUS implantation for PPI were reviewed. Patients who had bladder outlet obstruction surgery before radical prostatectomy or AUS-related complications that required revision of AUS within three months were excluded. Patients were divided into two groups based on the preoperative urodynamic study including pressure flow study, a DU group, and a non-DU group. DU was defined as a bladder contractility index less than 100. The primary outcome was postoperative postvoid residual urine volume (PVR). The secondary outcomes included maximum flow rate (Qmax), postoperative satisfaction, and international prostate symptom score (IPSS). Results: A total of 78 patients with PPI were assessed. The DU group consisted of 55 patients (70.5%) and the non-DU group comprised 23 patients (29.5%). Qmax was lower in the DU group than in the non-DU group and PVR was higher in the DU group as per a urodynamic study before AUS implantation. There was no significant difference in postoperative PVR between the two groups, although the Qmax after AUS implantation was significantly lower in the DU group. While the DU group showed significant improvements in Qmax, PVR, IPSS total score, IPSS storage subscore, and IPSS quality of life (QoL) score after AUS implantation, the non-DU group showed postoperative improvement in IPSS QoL score. Conclusion: There was no clinically significant impact of preoperative DU on the outcome of AUS implantation for PPI; thus, surgery can be safely performed in patients with PPI and DU.